Observer‐based H∞ control for uncertain singular time‐delay systems with actuator saturation. (7th September 2015) - Ma, Yuechao; Yan, Yifang
Summary: In this paper, the observer‐based H ∞ control problem for uncertain singular time‐delay systems with actuator saturation is concerned. First, a delay‐dependent linear matrix inequality (LMI) condition is obtained which, guarantees that the uncertain singular time‐delay systems with actuator saturation are regular, impulse free, and asymptotically stable with H ∞ performance condition. Then, with this condition, the estimation of stability region and the design method of observer‐based H ∞ controller are given by solving LMIs and convex optimization problem. Finally, some numerical examples are provided to demonstrate the merit of the obtained results. Copyright © 2015 John Wiley & Sons, Ltd.